Cow urine as a biopesticide and biorepellent: a systematic literature review (Research, Society and Development, 2020)
A systematic review of the literature was carried out on the potential of cow urine as a biopesticide and biorepellant in agriculture, providing information on its chemical composition, forms of application and results on bioefficacy in the control of different taxonomic groups. The mapping of scientific productions was carried out from March to August 2020 through the electronic bases: Portal of journals Capes, Pubmed and Scientific Eletronic Library Online (SciELO). English and Portuguese terms were used for the searches, with the following terms being used: Cattle urine, insects, cow urine, aphids, biopesticide, repellent, cow urine, repellent. The search coverage period was limited to the last 10 years. In total, 828 publications were counted. The Capes Periodic database showed 804 results. The Pubmed and SciELO databases showed 24 and zero results, respectively. Nine articles met the criteria and were selected. Of the total, 66% of selected publications were conducted in India. Of this total, 55, 5% of the studies used methodologies for collecting, preparing and using fresh urine; 33.3% used urine combined with plant extracts and 22.2% used urine in treatments of different concentrations. As for the action, 33.3% investigated the inhibitory action on phytopathogenic microorganisms (bacteria and fungi). Another 33.3% evaluated volatile compounds in urine and 22.2% measured the bio-repellent / bioinsecticide action on arthropod species (insects and arachnids). The discussions covered in this review contribute with information on the chemical composition, preparation, management and potential uses of cow urine as a biopesticide and biorepellent in agriculture.